Impact of MBL2 gene polymorphisms on the risk of infection in solid organ transplant recipients: A systematic review and meta‐analysis. Issue 4 (7th December 2018) - Fernández‐Ruiz, Mario; Giménez, Estela; Lora, David; Aguado, José María; Pascual, Manuel; Manuel, Oriol
Abstract : Mannose‐binding lectin (MBL) is a soluble pattern recognition molecule involved in complement activation. Single nucleotide polymorphisms (SNPs) in the MBL2 gene have been associated with susceptibility to infection, although data in solid organ transplant recipients remains inconclusive. This meta‐analysis was primarily aimed at investigating the association between posttransplant bacterial and fungal infection and variant alleles of MBL2 gene SNPs in the promoter/5' untranslated region and exon 1. Cytomegalovirus (CMV) infection and/or disease were considered secondary outcomes. PubMed, EMBASE, and Web of Knowledge were searched for relevant articles up to August 2018. Eleven studies (comprising 1858 patients) were included, with liver transplant (LT) recipients accounting for 80.4% of the pooled population. As compared to high‐MBL expression haplotypes (YA/YA, YA/XA), any MBL‐deficient haplotype was associated with an increased risk of posttransplant bacterial and fungal infections (risk ratio [RR]: 1.30; P = .04). Low/null‐MBL expression haplotypes (XA/O, O/O) also increased the risk of primary outcome (RR: 1.51; P = .008) and CMV events (RR: 1.50; P = .006). No effect was observed for individual promoter SNPs. In conclusion, MBL‐deficient haplotypes are associated with a significant, albeit moderate, increase in the risk of posttransplant infection, with this association being mainly restricted to LT recipients. Abstract : This systematic review and meta‐analysis finds that the presence of single nucleotide polymorphisms in the MBL2 gene, associated with defective production of mannose‐binding lectin, confers a significant, albeit moderate, increase in the risk of infection after solid organ transplantation.